Acquirable of Low-technological Devices for Learning in Special Schools - Obielodan Omotayo Olabo; Akomolafe Precious Oreoluwa; Onojah Amos Ochayi; Nuhu Kehinde Muritala; Onojah Adenike Aderogba (Indonesian Journal of Community and Special Needs Education, 2022)
All special students need to learn adequately so that their deviation from the norm will not demerit them from other students. Thus, there is a need for them to have enough learning tools which will help them achieve their academic goals. These technologies that aided the learning of special students are called low-technological devices. But when these technologies for special students are not sufficiently available, learning could be jeopardized. This study, therefore, investigates the available low-technological devices for learning in special secondary schools. This study employs the survey method and 150 secondary school students from special schools were purposively sampled. The findings established that revealed that Stylus, Picture symbols, Pocket dictionary/thesaurus, and Line guide are Highly available to the respondents but Wrist Rest, Signalling Device, Graph paper, and Adjustable Table and Hearing Aids are moderately available to the respondents accordingly. The study concluded that some recent and high technological devices are not adequately available. It was however recommended that Government should provide adequate funding to improve the availability and affordability of assistive technology for children with disabilities.